Single-level Discrete Two Dimensional Wavelet Transform Based Multiscale Deep Learning Framework for Two-Wheeler Helmet Detection - Amrutha Annadurai; Manas Ranjan Prusty; Trilok Nath Pandey; Subhra Rani Patra (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems)
INTRODUCTION: A robust method is proposed in this paper to detect helmet usage in two-wheeler riders to enhance road safety.